An analysis model for studying the determinants of throwing scoring actions during standing judo - Mayo, X.; Dopico-Calvo, X.; Iglesias-Soler, E. (Sports, 2019)
In judo, the attacking system is grounded on several determinants of the chances to throw. In our study, data regarding four determinants of the attacking system were collected in order to classify the standing scoring actions: the attacking type (direct/counter-attack), the throwing area (forward/backward), the technique`s category (based on motor criteria), and the lateral structure of fighting (contenders with a symmetrical/asymmetrical position). To study the usefulness of such an analysis, the standing scoring actions of the 2013 Judo World Championship were analyzed as an example of elite judo`s attacking system (n = 775). The Pearson`s chi-squared test and Cramér`s V were used to analyze the hypothesis of a uniform distribution or the association between variables and the strength of such an association, respectively. The scoring actions (p < 0.001) were mostly direct attacks (82.6%), in the forward throw area (57.5%), and in an asymmetrical position (67.2%). All of the variables were associated (p < 0.05; V = 0.11-0.54), with higher proportions of counter-attacks and attacks occurring on the backward thrown area during asymmetrical structures than the expected. Some categories of techniques were observed more than expected, depending on the symmetrical or asymmetrical structure. Our data augment the knowledge of standing judo by showing features of the attacking system, suggesting strategies for optimizing performance